Smith and Keenan's company law for students - Keenan, Denis; Smith, Kenneth (London; Financial Times Pitman Publishing, 1999)
Smith and Keenan's Company Law for Students" by Denis Keenan and Kenneth Smith is a highly recommended textbook for students of company law. It offers a clear and comprehensive overview of the subject, covering essential topics such as company formation, governance, directors' duties, and corporate finance. The book's structured approach, including case studies and practical examples, ensures that complex legal principles are presented in an accessible manner. Updated regularly to reflect current legal developments, it serves as an invaluable resource for both academic study and practical application in the field of company law.
Keywords: Corporate Governance; Case Studies